Design and test of post-seat weeding machine for paddy - Tian, Liang; Cao, Chengmao; Qin, Kuan; Fang, Liangfei; Ge, Jun (International Journal of Agricultural and Biological Engineering, 2021)
Aiming to solve problems in organic rice weeding a type of post-seat weeding machine was designed for rice paddies. The differences in the strengths and lengths of the root systems between the rice seedlings and the weeds were studied, and the motion track of the weeding wheel was analyzed to obtain the structural parameters of the weeding wheel. Then, the structural model of the weeding wheel was designed. The interaction process between the weeding wheel and soil in the paddy fields was simulated and analyzed based on the discrete element method, so as to investigate the working resistance change tendency of the weeding wheel and the orderliness of the soil disturbances. An orthogonal test was designed in this study, with three factors: the hoeing depth, the rotation rate of the weeding wheel, and the forward speed of the device. The influences of different operation parameters of the weeding machine on the weeding torque and soil disturbance speed were obtained based on a variance analysis of the test results. A multi-index comprehensive weighted scoring method was used to evaluate the simulation results. A soil bin test was conducted to verify the simulation results. Field experiments were carried out to test the working performance of the weeding machine. The comprehensive scoring results indicated that a better working performance of the weeding operation could be obtained when the hoeing depth was 50 mm, the rotation rate of the weeding wheel was 240 r/min, and the forward speed was 0.6 m/s. The results of the soil bin test were consistent with the simulation results. The results of the field experiment revealed that the weeding machine met the requirements for organic rice weeding. These results can provide a reference for the design of weeding machines for paddy fields.Keywords: paddy field, weeding, structural parameters, discrete element method, soilDOI: 10.25165/j.ijabe.20211403.5936Citation: Tian L, Cao C M, Qin K, Fang L F, Ge J. Design and test of post-seat weeding machine for paddy. Int J Agric & Biol Eng, 2021; 14(3): 112–122.